Molecular Dynamics Investigation of Graphene Nanoplate Diffusion Behavior in Poly-α-Olefin Lubricating Oil - Lupeng Wu; Baoyu Song; Leon M. Keer; Le Gu (Crystals, 2018)
Graphene as a type of novel additive significantly enhanced the tribological performance of blended lubricating oil. However, the dispersibility of graphene with long-term stability in lubricating oil is still a challenge. Chemical modification for graphene, rather than using surfactants, provided a better method to improve the dispersibility of graphene in lubricants. In this study, the equilibrium molecular dynamics (EMD) simulations were carried out to investigate the diffusion behavior of graphene nanoplates in poly-α-olefin (PAO) lubricating oil. The effects of graphene-size, edge-functionalization, temperature, and pressure on the diffusion coefficient were studied. In order to understand the influence of edge-functionalization, three different functional groups were grafted to the edge of graphene nanoplates: COOH, COON(CH3)2, CONH(CH2)8CH3 (termed GO, MG, and AG, respectively). The EMD simulations results demonstrated that the relationships between diffusion coefficient and graphene-size and number of functional groups were linear while the temperature and pressure had a nonlinear influence on the diffusion coefficient. It was found that the larger dimension and more functional groups provided the lower diffusion coefficient. AG with eight CONH(CH2)8CH3 groups exhibited the lowest diffusion coefficient. Furthermore, the experimental results and radial distribution function for graphene-PAO illustrated that the diffusion coefficient reflected the dispersibility of nanoparticles in nanofluids to some degree. To our best knowledge, this study is the first time the diffusion behavior of graphene in PAO lubricating oil was investigated using EMD simulations.